Egemonia e gerarchia, tracce nei «Quaderni del carcere» - Solinas, Piergiorgio (International Gramsci Journal, 2023)
We attempt a reading of Gramsci’s Prison Notebooks through the filter of certain specific categories: the “organic”, the “collective will” and “hierarchy”. A number of problematic links are proposed between the social and cultural dimensions of the approaches to the image of the people, classes and power. So far, the anthropological reception of the Notebooks had been confined within the possible codes of translation (culture / Weltanschauung; social morphology / class structure; enculturation / consciousness, and so on). My comments here seek an inner meaning of praxis as a science of power, power physiology and model of its relation with social consciousness as a possible paradigm for our anthropological understanding. From this specific perspective, the category of hierarchy appears as a possible dynamic concept reshaped by the modernized systems of consensus and the nurturing of ordinary scales of inequality: voluntary and ethically approved degrees of social value, participation in submission, and support of and communal trust in values and cultural patterns. Is Gramsci’s theory of collective thought and “organic” cohesion an efficient device for contemporary social science? It would be desirable for a lay approach to the vertical dimension of culture as a valued tool of the social self to be made useful to the present.